Interactive mathematical learning courseware 2.0 using mental arithmetic for preschool children / Siti Zulaiha Ahmad ... [et al.] - Rosmani, Arifah Fasha; Ismail, Mohammad Hafiz; Mazlan, Umi Hanim (UiTM Perlis, 2014)
Interactive Mathematical Learning Courseware 2.0 (iMLc 2.0) is an enhanced version of multimedia application which the aim is to expose the pre-school children in mental arithmetic technique. Unlike other form of conventional application which are using traditional methods, iMLc 2.0 display highly efficient technique to users who are at early stage of learning mathematics. The application integrates multimedia elements and mental arithmetic technique in an interactive and supportive way that is suitable for pre-school children level. Six multimedia principles have been adapted into the application in order to enhance the interface design. The application is divided into three modules, addition, subtraction, and quizzes. The addition operation has been designed to apply the finger-brain approach which is part of mental arithmetic technique while, mental-imagery approach is adapted for subtraction operation. In order to evaluate the application, it goes through a series of testing which are experimental test and user acceptance test. Mathematical courseware application can be used as additional learning and teaching tools since it is interesting, user friendly, enjoyable, valuable, and supportive. The implementation of iMLc 2.0 using interactive multimedia environment can motivate the preschooler to be prepared for future mathematical learning.